2011
DOI: 10.1007/s10152-011-0256-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the taxonomy of Hypanis (Bivalvia, Cardiidae, Lymnocardiinae) in the Black Sea lagoons

Abstract: In this study, we used data from morphology and three DNA markers to assess the taxonomic status of the putative bivalve species Hypanis colorata and Hypanis angusticostata in a Black Sea lagoon, the Razelm Lake in Romania. The morphological data (the shape of shell ribs and the multivariate analysis of morphometric variance of three variables constructed as the ratios between the main dimensions of the shell) conWrmed that the two analyzed species are distinct morphological entities. Three molecular markers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It has recently been shown that many nominal taxa of fresh- and brackish-water snails and mussels described on the basis of their shell characters (the Pontocaspian molluscs rarely were described on the base of anatomical studies) lack a genetic support (with few exceptions such as e.g., Popa et al 2012, Stepien et al 2013) and thus do not represent evolutionary meaningful units. On the other hand, cryptic speciation is known within many taxa of molluscs in long-lived lakes (Albrecht et al 2006), and the Pontocaspian biota may include some previously unrecognised species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has recently been shown that many nominal taxa of fresh- and brackish-water snails and mussels described on the basis of their shell characters (the Pontocaspian molluscs rarely were described on the base of anatomical studies) lack a genetic support (with few exceptions such as e.g., Popa et al 2012, Stepien et al 2013) and thus do not represent evolutionary meaningful units. On the other hand, cryptic speciation is known within many taxa of molluscs in long-lived lakes (Albrecht et al 2006), and the Pontocaspian biota may include some previously unrecognised species.…”
Section: Discussionmentioning
confidence: 99%
“…Often, such distinctions are made based on the geographical isolation alone or on a range of morphological characters whose variation seems to be overlapping in geographical subpopulations. In order to assess whether the geographical populations are indeed species, we need combined morphological, ecological, and molecular data, but only few studies produced this information to date (e.g., Popa et al 2012 for Black Sea Basin Monodacna ). For the Aral Sea, we expect difficulties to obtain fresh material of almost all species for molecular analyses due to the obliteration of most of the lake and its fauna in the 20 th century (Andreeva and Andreev 2003, Plotnikov et al 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In several recent works Monodacna and Adacna are considered to be subgenera of Hypanis (e.g. Popa et al, 2011). In other works (e.g.…”
Section: Discussionmentioning
confidence: 99%